PENGGUNAAN VIDEO PEMBELAJARAN PADA PEMBELAJARAN GEOGRAFI TERHADAP HASIL BELAJAR SISWA KELAS X SMA - Umarul Mu’min; Budiman Tampubolon; Putri Tipa Anasi (Universitas Tanjungpura, 2020)
AbstractThis study aims to determine the effect used of learning videos on geography learning on student learning outcomes of class X Islamic Senior High School Haruniyah Pontianak. The study method used is an experimental method with a form of research Quasi Experimental Design with the design of Nonequivalent Control Group Design. The population of this study was all students of class X IIS Islamic Senior High School Haruniyah Pontianak, amounting to 58 people. The sampling technique used is simple random sampling. Based on the calculations, the average results of the final test of the experimental class were 80.13 and the average final test of the control class was 69,36. Hypothesis test results using the t-test is tcount of 3.113 and ttable of 1.672. Based on tcount> ttable Ha is accepted. So, the above calculation can be concluded that there are differences in the learning outcomes of students in grade X Islamic Senior High School Haruniyah Pontianak who used video learning and image media. Based on the calculation of the effect size obtained an ES of 0.773. Video learning geography gives a medium influence on student learning outcomes class X Islamic Senior High School Haruniyah Pontianak.Keywords: Learning Geography, Learning Videos, Learning Outcomes.